1993
DOI: 10.1901/jeab.1993.60-293
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Control on Interval Schedules: What Determines the Postreinforcement Pause?

Abstract: On fixed-interval or response-initiated delay schedules of reinforcement, the average pause following food presentation is proportional to the interfood interval. Moreover, when a number of intervals of different durations occur in a programmed cyclic series, postreinforcement pauses track the changes in interval value. What controls the duration of postreinforcement pauses under these conditions? Staddon, Wynne, and Higa (1991), in their linear waiting model, propose control by the preceding interfood interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 14 publications
2
15
0
Order By: Relevance
“…We suggest that rats are just trying to preserve the overall reinforcing rate. Indeed, any portion of time elapsed because of imposed delays is reflected by a nearly equivalent narrowing of the spontaneous waiting (RT), as predicted according to a linear waiting model (Innis and Staddon, 1971; see also Innis et al, 1993;Ludvig and Staddon, 2004;Staddon and Cerutti, 2003). However, when delay lengths are further increased (i.e.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…We suggest that rats are just trying to preserve the overall reinforcing rate. Indeed, any portion of time elapsed because of imposed delays is reflected by a nearly equivalent narrowing of the spontaneous waiting (RT), as predicted according to a linear waiting model (Innis and Staddon, 1971; see also Innis et al, 1993;Ludvig and Staddon, 2004;Staddon and Cerutti, 2003). However, when delay lengths are further increased (i.e.…”
Section: Discussionmentioning
confidence: 93%
“…There is considerable literature on rat's spontaneous waiting before initiating the next trial. A formal model of voluntary waiting, termed "linear waiting model", has been developed Innis et al, 1993). These authors demonstrated that duration of pauses following food presentation (termed post-reinforcement pauses, PRP) was determined by the preceding inter-food interval.…”
Section: Introductionmentioning
confidence: 99%
“…Under cyclic FI schedules, when the changes in interval length are orderly, this pause tracks changes in interval length. Innis, Mitchell, and Staddon (1993), using responseinitiated delay schedules with pigeons, showed that the just-experienced IFI influenced pause duration rather than the upcoming one, and they also found that earlier intervals might also have some influence. This was not the effect seen under the present procedure with FR schedules.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Innis et al (1993) provides a dynamic test of the linear waiting hypothesis as applied to chain schedules. Innis et al studied two-link chain schedules with one link of fixed duration and the other varying from reinforcer to reinforcer according to a triangular cycle.…”
Section: Chain Schedulesmentioning
confidence: 99%